DIE ROL VAN DIE UNIEVERDEDIGINGSMAG IN DIE ONDERDRUKKING VAN DIE NYWERHEIDSONLUSTE VAN JANUARIE 1914 - Jacobs, C.J. (Scientia Militaria - South African Journal of Military Studies, 2012)
During the Railways and Mineworkers strike which commenced on the 18th of January 1914, the Union Defence Force, enlarged by the Active Citizen Force and assisted by the Commandos, were able to take immediate action and suppress the riots. The strike was also excellent preparation of the Union Defence Force for their participation in the First World War and the suppression of the ensuing Rebellion of 1914/15. It clearly illustrated the value of an own Defence Force, in that it would no longer be necessary to make use of Imperial troops for the defence of South Africa.